2002
DOI: 10.2174/1568026023393426
|View full text |Cite
|
Sign up to set email alerts
|

GABA-A Receptors as Molecular Sites of Ethanol Action. Direct or Indirect Actions?

Abstract: Despite the fact that ethanol is one of the most widely used psychoactive agents, the mechanisms and sites of action by which it modifies brain functions are only now being elucidated. Studies over the last decade have shown that ethanol can specifically alter the function of several ligand-activated ion channels including N-methyl-D-aspartate (NMDA), serotonin (5-HT(3)), glycine and GABA(A) receptors. After several years of extensive research in this field, the resolution of what, where and how ethanol modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 0 publications
7
86
0
2
Order By: Relevance
“…The focus of research on the interactions of ethanol with the GABA system has been on GABA A receptors (27). However, it also has been shown that inwardly rectifying potassium channels coupled to GABA B receptors are targets of alcohol action in CNS neurons (28) and that GABA B receptors may participate in long-lasting potentiation of GABAergic synapses after a single in vivo ethanol exposure (29).…”
Section: Discussionmentioning
confidence: 99%
“…The focus of research on the interactions of ethanol with the GABA system has been on GABA A receptors (27). However, it also has been shown that inwardly rectifying potassium channels coupled to GABA B receptors are targets of alcohol action in CNS neurons (28) and that GABA B receptors may participate in long-lasting potentiation of GABAergic synapses after a single in vivo ethanol exposure (29).…”
Section: Discussionmentioning
confidence: 99%
“…This point is illustrated in Figure 2. The topic of ethanol action on GABA A receptors has been reviewed by Aguayo et al (2002).…”
Section: In Vitro Examination Of Ethanol Action On Gaba a Receptor Fumentioning
confidence: 99%
“…First, did alcohol bind directly to GABA A receptors, or did it somehow potentiate GABA indirectly? Although several groups observed similar effects of alcohol on GABA A receptor activity measured using 36 Cl Ϫ flux in synaptoneurosomes (7,13), many, if not most, electrophysiological studies simply failed to find direct alcohol-induced augmentation of GABA-mediated synaptic events (5,14). Second, was the imidazobenzodiazepine ''alcohol antagonist'' Ro15-4513 really a ''selective'' alcohol antagonist, or did it merely reverse some of the biochemical, electrophysiological, and behavioral effects of alcohol by virtue of its inverse agonist properties (15,16), i.e., by simply producing the opposite effects of alcohol?…”
Section: Alcohol and Gabamentioning
confidence: 99%